2005
DOI: 10.1021/cm048292g
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Optical Properties of Lemongrass Extract Synthesized Gold Nanotriangles and Potential Application in Infrared-Absorbing Optical Coatings

Abstract: Anisotropic metal nanoparticles have distinct optical behavior when compared with their spherical counterparts. In this report, we demonstrate a simple method involving the reduction of aqueous gold ions by the extract of the lemongrass plant leading to the formation of gold nanotriangles with interesting absorption in the near-infrared (NIR) region of the electromagnetic spectrum. We show that, by simple variation of the experimental conditions, it is possible to vary the size of the gold nanotriangles and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
398
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(417 citation statements)
references
References 29 publications
17
398
1
1
Order By: Relevance
“…Recently, several plants extracts such as Annona squamosa [16], Arbutus unedo [17], Cassia angustifolia [18] and many others [19][20][21][22][23][24][25][26][27] have been used to synthesize silver (Ag) and gold (Au) nanoparticles (NPs). However, these natural sources, which have active ingredients, produce nanoparticles at slower rate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several plants extracts such as Annona squamosa [16], Arbutus unedo [17], Cassia angustifolia [18] and many others [19][20][21][22][23][24][25][26][27] have been used to synthesize silver (Ag) and gold (Au) nanoparticles (NPs). However, these natural sources, which have active ingredients, produce nanoparticles at slower rate.…”
Section: Introductionmentioning
confidence: 99%
“…Jose-Yacaman and co-workers (Gardea-Torresdey et al 2002 first reported the formation gold and silver nanoparticles by living plants. Green silver nanoparticles have been synthesized using various natural products, such as green tea (Camellia sinensis) (Vilchis-Nestor et al 2008), neem (Azadirachta indica) leaf broth (Shiv Shankar et al 2004), natural rubber (Abu Bakar et al 2007), starch (Vigneshwaran et al 2006), aloevera plant extract (Chandran et al 2006), lemongrass leaves extract (Shankar et al , 2005 leguminous shrub (Sesbania drummondii) (Sharma et al 2007), mushroom extract (Philip 2009), Coleus amboinicus lour (Narayanan andSakthivel 2011), Medicago sativa (Lukman et al 2011), and Citrus sinensis peel (Kaviya et al 2011) to name few. Shankar et al (2004) and Shiv Shankar et al (2004) reported the metallic silver and gold nanoparticle synthesis by using Neem (Azadirachta indica) leaf broth.…”
Section: Introductionmentioning
confidence: 99%
“…The flower-shape gold nanoparticles are synthesized without the use of toxic chemicals and stabilizers. Literature survey revealed synthesis of biological triangular gold nanoprisms by the reduction of aqueous chloroaurate ions by extracts of Cymbopogon flexuosus in high yield at room temperature [35]. Tamarind leaf extract can also be used as the reducing agent for making gold nanotriangles [36].…”
Section: Tem Analysismentioning
confidence: 99%